Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376226
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction Design for Machine Teaching to Develop AI Tutors

Abstract: Intelligent tutoring systems (ITSs) have consistently been shown to improve the educational outcomes of students when used alone or combined with traditional instruction. However, building an ITS is a time-consuming process which requires specialized knowledge of existing tools. Extant authoring methods, including the Cognitive Tutor Authoring Tools' (CTAT) example-tracing method and SimStudent's Authoring by Tutoring, use programming-by-demonstration to allow authors to build ITSs more quickly than they could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We believe that learning technology should be humancentered because it aims at teaching and interactive activities. The HCAI approach now taking shape aims to enhance human capabilities, such as by allowing teachers to build their own computerized lessons using insights gathered from an AI tutoring system (Weitekamp et al, 2020). AI-supported learning environments therefore must not only focus on performance, but also human emotions and outcomes should be main concerns.…”
Section: A Human-centered Ai Approach In Educationmentioning
confidence: 99%
“…We believe that learning technology should be humancentered because it aims at teaching and interactive activities. The HCAI approach now taking shape aims to enhance human capabilities, such as by allowing teachers to build their own computerized lessons using insights gathered from an AI tutoring system (Weitekamp et al, 2020). AI-supported learning environments therefore must not only focus on performance, but also human emotions and outcomes should be main concerns.…”
Section: A Human-centered Ai Approach In Educationmentioning
confidence: 99%
“…As a result, in the present study, self-reported student performance (grades), self-reported student progress (improved knowledge and confidence), and self-reported use and usefulness were investigated. Intelligent tutoring systems (ITS) have been consistently shown to improve students' educational outcomes when used alone or combined with traditional instruction [44]. Likewise, intelligent tutoring system (ITS) technology, example follow-up tutors that can be generated without programming alone using cognitive tutor authoring tools (CTAT) [45].…”
Section: Research Articlementioning
confidence: 99%
“…As more examples are encountered the where-part of a skill tends to propose more and more candidate bindings, but it typically avoids overgeneralizing beyond what the examples so far entail. 6 The the AL where-learning mechanism described in [64] generalizes wherepart matching conditions by performing simple anti-unification. In this wherelearning mechanism, called 'AntiUnify', a set of conjunctive conditions are maintained that check for particular features or spatial relationships (i.e.…”
Section: Algorithmic-levelmentioning
confidence: 99%
“…In the multi-column addition example shown in Figure 5 these neighboring elements are eliminated upon generalization, however, in some circumstances these neighbor elements can remain and are essential to keeping where-learning from over-generalizing. For example, continuing with the example of multi-column addition, for skills that carry '1's across columns, neighboring elements help form an adjacency relationship between 6 Historically AL and SimStudent's where-learning mechanisms have been described as implementing version spaces [39] [36] [32] [64]. However, least general generalization is a better characterization since version spaces implement both general-to-specific and specific-to-general learning, but where-learning has historically only implemented the latter (section 6 describes why this is the case).…”
Section: Algorithmic-levelmentioning
confidence: 99%